PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA (Studi Empiris Perusahaan Consumer Good Yang Terdaftar Di BEI Periode 2015-2019) - Rico Nur Ilham; Debi Eka Putri; Mangasi Sinurat; Likdanawati Likdanawati; Irada Sinta (ITB AAS INDONESIA, 2022)
This study analyzed the effects of financial ratios (CR, DER, TATO, and NPM) on changes in profits in consumer goods companies listed on the Indonesia Stock Exchange. The population in this study was all continuously registered Consumer Goods companies in 2015-2019, while the samples used as the object of research amounted to 15 companies using the purposive sampling technique. The model used in the data analysis was panel data regression with the help of Eviews 10. The results indicated that only NPM had a positive and significant effect on changes in earnings changes while the CR, DER, and TATO had no significant effect on earnings changes.